SPAR Profiles for the Assessment of Genetic Diversity Between Male and Female Landraces of the Dioecious Betelvine Plant (Piper betle L.) - Ranade, Shirish A.; Soni, Anjali; Kumar, Nikhil (IntechOpen, 2011)
None